Lipidomics profile of irradiated ground meat to support food safety. (1st May 2022) - Chiesa, Luca Maria; Di Cesare, Federica; Mosconi, Giacomo; Pavlovic, Radmila; Campaniello, Maria; Tomaiuolo, Michele; Mangiacotti, Michele; Chiaravalle, Eugenio; Panseri, Sara
Highlights: HPLC-Orbitrap lipidomics of irradiated meat was used for the food safety purposes. Irradiation of chicken, turkey and mixed ground meat resulted in lipidome alterations. Chicken, turkey and mixed ground meat were distinctly influenced by irradiation. Characteristic oxidized phospholipids were identified in turkey irradiated meat. Abstract: Meat irradiation is considered as an effective treatment that expose the advantageous effects on meat preservation. This research, based on untargeted LC-HR orbitrap MS-based lipidomics strategy was meant to estimate the alterations in lipid profile of irradiated chicken, turkey and mixed (chicken, turkey and pork) ground meat in order to evaluate if exists any food safety issue concerning the lipidome alteration. Special attention was paid on oxidation triggered by irradiation. All three matrices exhibited a characteristic lipidome profile which was affected differently by five levels of irradiation intensity. Overall, 345 lipids categorized into 14 subclasses were identified. Remarkably, the oxidized glycerophosphoethanolamines and oxidized glycerophosphoserines were identified in irradiated turkey meat, while for all three categories a characteristic diacylglycerols profile was recognised. Our analytical approach highlighted that the estimation of qualitative variations in lipid portion might be valuable in food inspection purposes, especially when the samples from animal origin are suspected on irradiation treatment.